A Critical Review of Don Gibson's Theory Regarding the Geographical Location of Well of Zamzam - Nisar Ahmad; Dr. Javed Khan (Journal of Religion and Society, 2025)
This paper critically examines Dan Gibson’s controversial hypothesis that challenges the traditional Islamic belief that Mecca is the original sacred city, proposing instead that Petra in Jordan holds this distinction. Gibson’s theory involves relocating key Islamic religious sites, including the Well of Zamzam, from Mecca to Petra, based on his analysis of early Islamic texts and geographical inconsistencies. The study outlines the historical and religious significance of the Well of Zamzam within Islamic tradition and contrasts it with Gibson’s arguments, which link the Zamzam well to a spring near Petra, drawing on biblical references to the Zamzummim people and Petra’s reputation as the "City of Cisterns." A critical evaluation reveals significant weaknesses and contradictions in Gibson’s claims, particularly regarding the geographical disconnect between the Zamzummim territory and Petra, and the flawed reasoning that associates Petra’s cisterns with the Zamzam well. The paper concludes that Gibson’s arguments lack substantial evidence and do not convincingly challenge the established understanding of Mecca as the holiest city in Islam. Keywords: The Well of Zamzam, Mecca, Quranic Geography, Dan Gibson, Orientalism